Investigation of a Pharmacological Approach for Reduction of Renal Uptake of Radiolabeled ADAPT Scaffold Protein; Molecules; Vol. 25, iss. 19 - Vorobjeva (Vorobyeva) A. G. Anzhelika Grigorjevna; Oroujeni M. Maryam; Lindbo S.; Hober S. Sophia; Xu T. Tianqi; Liu Y. Yongsheng; Rinne S. S. Sara; Garousi J. Javad (2020, 2020)
Title screen